Gas‐Responsive Self‐Assemblies for Mimicking the Alveoli. Issue 18 (14th March 2021) - Guo, Xiaofeng; Ji, Xianfeng; Li, Xuehai; Du, Jinhong; Sun, Lulu; Feng, Anchao; Yuan, Jinying; Thang, San H.
Abstract: In human body, alveoli are the primary sites for gas exchange which are formed by the dilation and protrusion of bronchioles at the end of the lung, and the rapid gas‐exchanging process in the alveoli ensures normal life activities. Based on the unique structures and functions of alveoli, it is necessary to study the regulation mechanism of its formation, respiration, and apoptosis. Herein, a class of reversible addition−fragmentation chain transfer (RAFT)‐derived amphiphilic triblock copolymers, PEO‐ b ‐P(DEAEMA‐ co ‐FMA)‐ b ‐PS is designed and synthesized. Due to the amphiphilic and gas‐responsive segments, these triblock copolymers can self‐assemble in aqueous solution and undergo the morphological transition from nanotubes to vesicles under gas stimulation; meanwhile, in the cycles of CO2 /O2 stimulation, these vesicles can further realize the volume expansion and contraction, eventually rupture. The gas‐driven morphological transformations of these aggregates successfully imitate the formation, respiration, and apoptosis of alveoli, and provide an essential basis for revealing the life phenomena. Abstract : This work demonstrates the synthesis of a dual gas‐responsive polymeric vesicle system via self‐assembly of the O2 and CO2 ‐sensitive amphiphilic triblock copolymers PEO‐ b ‐P(DEAEMA‐ co ‐FMA)‐ b ‐PS. The gas‐driven morphology change and shape transformation of these aggregates successfully simulate the formation, respiration, and apoptosis of alveoli, also provide a new way for revealing the life phenomena.